O marketing teatral na cidade de Lorena - SP - SILVA, Eliabe Henrique Carneiro da; MARQUES, Kauã Rodriques; FERREIRA, Larissa da Silva; SANTOS, Maria Rita de Paula dos (240, 2023)
Este artigo investiga a conexão entre teatro e marketing em Lorena, destacando a redução do interesse local em estratégias promocionais. Procura compreender as origens desse declínio e sugere soluções inovadoras, utilizando o Teatrim Cultura e Arte como estudo de caso. Diante de obstáculos como a carência de acesso ao teatro e estratégias de marketing pouco eficazes, a meta é enriquecer culturalmente a região e fomentar uma maior valorização da expressão teatral.

This article delves into the correlation between theater and marketing in Lorena, emphasizing the waning local enthusiasm for promotional approaches. It aims to comprehend the roots of this decline and proposes inventive solutions, employing Teatrim Cultura e Arte as a case study. Confronted with challenges like limited access to theater and ineffective marketing strategies, the objective is to culturally enhance the region and foster a heightened appreciation for theatrical expression.
The traditional marketing of theater today in Lorena
Keywords: Marketing; Marketing cultural; Teatro; Gestão e Negócios